Unemployment and Health-Related Quality of Life in Melanoma Patients During the COVID-19 Pandemic - Guo, Yeye; Shen, Minxue; Zhang, Xu; Xiao, Yi; Zhao, Shuang; Yin, Mingzhu; Bu, Wenbo; Wang, Yan; Chen, Xiang; Su, Juan (Frontiers in Public Health, 2021)
The outbreak of coronavirus disease-2019 (COVID-19) ineluctably caused social distancing and unemployment, which may bring additional health risks for patients with cancer. To investigate the association of the pandemic-related impacts with the health-related quality of life (HRQoL) among patients with melanoma during the COVID-19 pandemic, we conducted a cross-sectional study among Chinese patients with melanoma. A self-administered online questionnaire was distributed to melanoma patients through social media. Demographic and clinical data, and pandemic-related impacts (unemployment and income loss) were collected. HRQoL was determined by the Functional Assessment of Cancer Therapy-General (FACT-G) and its disease-specific module (the melanoma subscale, MS). A total of 135 patients with melanoma completed the study. The mean age of the patients was 55.8±14.2 years, 48.1% (65/135) were male, and 17.04% (34/135) were unemployed since the epidemic. Unemployment of the patients and their family members and income loss were significantly associated with a lower FACT-G score, while the MS score was associated with the unemployment of the patients’ family members. Our findings suggested that unemployment is associated with impaired HRQoL in melanoma patients during the COVID-19 epidemic.